2004
DOI: 10.1002/ccd.20190
|View full text |Cite
|
Sign up to set email alerts
|

Use of suture‐mediated vascular closure devices for the management of femoral vein access after transcatheter procedures

Abstract: Groin complications remain the most common complication of cardiac catheterization procedures. While the use of closure devices is increasing for arterial sheaths, venous sheaths tend to be removed and hemostasis achieved with manual compression. We report our experience using Perclose suture-mediated vascular closure device to achieve hemostasis and early mobility in patients who have had venous access as part of their procedure. There were a total of 42 patients (21 males; average age, 63.5 years) studied. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 10 publications
2
43
0
Order By: Relevance
“…There are two previously reported series on the use of closure devices in venous sites,3 4 one of which used an earlier version of the Perclose device4 in which the majority had 7Fr sheaths. In contrast to previous studies3 4 the devices were predeployed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There are two previously reported series on the use of closure devices in venous sites,3 4 one of which used an earlier version of the Perclose device4 in which the majority had 7Fr sheaths. In contrast to previous studies3 4 the devices were predeployed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other devices, this device can achieve a high degree of success even in patients who receive anticoagulation. 22,48,[58][59][60][61][62] An unusual complication of femoral arteritis has been reported with early platform of Perclose device which used a braided suture. 48,69,70 The introduction of the ProGlide model, which incorporated an improved suture trimming mechanism and replaced braided suture with monofilament polypropylene suture, has reduced the incidence of device failure and lowered the risk of infectious complication.…”
Section: Clinical Experience With Vascular Closure Devicesmentioning
confidence: 97%
“…While several clinical studies reported device success rates ranging from 90% to 100% which is similar to other devices. 22,48,[58][59][60][61][62] Device failure, while uncommon, has been attributed to suture breakage or failure to create a secured knot. If the Perclose device fails, MC can achieve hemostasis.…”
Section: Clinical Experience With Vascular Closure Devicesmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of the Perclose (Abbott Vascular Devices, Redwood City, CA) suture-mediated device for femoral vein access site closure following large (>8 Fr) sheath insertion was associated with a 98 % success rate of immediate (within 2 min) hemostasis in a wide range of congenital and structural cardiac interventions [16][17][18][19]. In one report, the Angio-Seal (St. Jude Medical, Minnetonka, MN) collagen-mediated, anchor-based vascular sealing device was found safe and successful for femoral venous hemostasis (in patients with venous sheaths ≤8 Fr), with no major complications, even in the presence of anticoagulation and antiplatelet agents [20].…”
Section: Prior Studies Of the F-8 Suture Techniquementioning
confidence: 99%